Possibility of 99mT c production at neutron generator - Dovbnya, A.N.; Kuplennikov, E.L.; Tsymba, V.A.; Krasil’nikov, V.V. (Вопросы атомной науки и техники, 2009)
Possibility of application of the neutron generator with intensity of a thermal neutrons flux 10¹² n · cm⁻² · s⁻¹ for 99mT c production is considered. Estimations are made on the base of ⁹⁸Mo(n, γ) ⁹⁹Mo → 99mT c nuclear reaction.